Comparative Analysis of Soil Fertility, Productivity and Sustainability of Organic Farming in Central Europe—Part 1: Effect of Medium Manifestations on Conversion, Fertilizer Types and Cropping Systems - Hartmut Kolbe (Agronomy, 2022)
Organic farming systems have become widespread in recent decades due to their popularity with consumers and their beneficial effects on the environment and biodiversity. Through the increasing number of available studies from farm surveys and comparable results from long-term field trials, the various real existing forms and intensities of agricultural management were subjected to a closer examination in this review. In this paper, the mean characteristics and the range of variation in crop productivity, crop quality and soil fertility as well as the importance and the extent of environmental impacts are comparatively analyzed. From widespread cultivation systems and forms of nutrient management from Central Europe with a focus on Germany, the following fields of influence were investigated and conclusions for the future optimal design of organic cultivation methods were listed: site, soil conditions, climate, phases of conversion and consolidation, crop rotations and farm structures, application of organic and mineral fertilizer types.